2016
DOI: 10.1177/0095798415597840
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Utilizing Black History Knowledge as a Path to Psychological Liberation for Black Youth

Abstract: Several scholars suggest that Black history knowledge (BHK) is a significant psychological strength that facilitates mental health for Black people, and Black youth in particular, as they face racial injustice and adversity. Yet no framework has been presented in the psychological literature to advance scholarship regarding the significance of BHK. While other constructs (e.g., racial identity and racial socialization) importantly highlight the significance of history, they are limited in accounting for the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…We found that most students in our sample reported themes related to psychological empowerment as being particularly significant to their experiences in BSCs. Prior theorizing and empirical research suggest that learning spaces that emphasize increased knowledge of Black heritage and culture are related to feelings of resilience and agency among Black students (Adams, 2005(Adams, , 2014Chapman-Hilliard & Adams-Bass, 2016;Livingston et al, 2010). In relation to their own empowerment experiences, participants consistently spoke about how learning the narratives of African-descent people across the diaspora stimulated feelings of competence and contributed to their self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that most students in our sample reported themes related to psychological empowerment as being particularly significant to their experiences in BSCs. Prior theorizing and empirical research suggest that learning spaces that emphasize increased knowledge of Black heritage and culture are related to feelings of resilience and agency among Black students (Adams, 2005(Adams, , 2014Chapman-Hilliard & Adams-Bass, 2016;Livingston et al, 2010). In relation to their own empowerment experiences, participants consistently spoke about how learning the narratives of African-descent people across the diaspora stimulated feelings of competence and contributed to their self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…While racial identity has been explored extensively in Black learners, its connection to participation in BSCs requires more exploration. One of the few investigations that quantitatively examined the influence of BSCs on Black learners found that individuals reporting exposure to BSCs tended to endorse higher racial and ethnic identity scores (i.e., participants reported race as central to their self‐concept, an interest in learning more about one's culture, and a strong affective connection with their cultural group) when compared to same‐race peers who had not taken BSCs (Chapman‐Hilliard et al, ). Hence, examining BSCs as a source for facilitating identity development and racial socialization is important considering that shifts in one's racial and cultural identity are foundational to the Black studies effect.…”
Section: Examining the Black Studies Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…In our approaches to youth, we must be mindful of dimensions of power and the imbalance in the control of services that may lead to unintended exclusion and oppression [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. Evidence-based health promotion programs may inadvertently cause harm by omission of antiracist practices [ 27 , 28 ].…”
Section: Integrating Antiracism Into Trauma-sensitive Care For Positimentioning
confidence: 99%
“…Traditionally, this work was grounded in racist assumptions that white children's identity development was normative, and that of children of color was “pathological” (Spencer & Markstrom‐Adams, ). In contrast, scholars like Cross and others (see Cross, for review) put forth psychological theories of black liberation identity development, which like Erikson, were comprised of various developmental stages but did not conceptualize black children as “pathological” (for an extensive review of literature on black psychology for liberation, see Chapman‐Hilliard & Adams‐Bass, ). Sociologists have also challenged underlying assumptions about developmental stages, such the important study conducted by sociologists Van Ausdale and Feagin () in which they explored the limits of Piaget's () stages of development.…”
Section: Four Focal Areasmentioning
confidence: 99%